Validity and reliability of an objective test of cricket skills - Stretch, Richard Aldworth (Rhodes University, Faculty of Science, Department of Human Movement Studies, 1985)
This study was conducted to assess the validity and reliability of four self-designed, objective tests of cricket batting, bowling, fielding and general ability skills. The batting test requires the batsman to hit a suspended ball at a target area as many times as possible in 60 seconds. His score is doubled to give his score for the batting test. In the bowling test the bowler is required to bowl ten balls at target areas marked on the pitch. Each delivery is recorded to give him a score out of 100. The fielding test requires the fielder to catch and field seven balls in a predetermined sequence. Each fielded ball that is not thrown through the target area incurs a penalty of three seconds. The total time taken is used to obtain the fielding test score out of 100. In the general ability test the player is required to hit a ball up and down twenty-five times. He then has to run along a predetermined path and field three balls and then bowl three balls at a target. A penalty of three seconds is added onto the time taken for each ball that does not pass through the target area. The actual score, out of 100, is determined from the total time taken. To determine the validity of the objective tests of batting, bowling, fielding and general ability, 155 subjects were subjectively assessed in these four categories by experienced coaches. The four objective tests were then conducted on these subjects and the scores compared. Forty-four subjects were assessed by experienced and inexperienced testers to determine the reliability of the tests when administered by different testers. To determine the reliability of the tests when repeatedly administered by one tester 23 subjects were assessed on five consecutive days. Significant correlations (p < 0,05) were found for the tests of validity between subjective and objective assessment (0,43 to 0,81) and the test for objectivity between experienced and inexperienced testers (0,41 to 0,78). A significant improvement (p < 0,05) in scores occurred during repeated testing, but most of this improvement took place between the first two tests. The results indicate that the tests are valid and reliable tests of cricket batting, bowling, fielding and general ability, if sufficient pre-test practice is allowed.
Keywords: Cricket; Cricket -- Training; Athletic ability -- Testing